Identification and control of an oxygen provider system for a biological capsule. Issue 1 (1st January 2017) - Mehne, H.H.
Abstract: Providing oxygen is a necessary process in manned missions to space. The aim of this paper is to identify the dynamics of an open loop control system in preparation for feature missions. A linear time invariant model is identified with data gathered from pre-flight tests of Kavoshgar, the Iranian bio-capsule. Numerical evaluation of the resulting model and its validation are given. The resulting time discrete model is used to drive the optimal setting that minimizes power consumption of the system.